2005
DOI: 10.1073/pnas.0505172102
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio bias, male aggression, and population collapse in lizards

Abstract: The adult sex ratio (ASR) is a key parameter of the demography of human and other animal populations, yet the causes of variation in ASR, how individuals respond to this variation, and how their response feeds back into population dynamics remain poorly understood. A prevalent hypothesis is that ASR is regulated by intrasexual competition, which would cause more mortality or emigration in the sex of increasing frequency. Our experimental manipulation of populations of the common lizard (Lacerta vivipara) shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
442
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(479 citation statements)
references
References 37 publications
12
442
1
1
Order By: Relevance
“…This hypothesis is supported by experimental studies, which indicate that male aggression toward females increases as a result of increased male–male competition in populations with male‐biased ASRs (Chapman, Arnqvist, Bangham, & Rowe, 2003; Le Galliard, Fitze, Ferrière, & Clobert, 2005), and this may be the main driver of female dispersal in some butterfly populations (Hovestadt & Nieminen, 2009). This process is hypothesized to be the evolutionary outcome of a sexual conflict over mating and reproduction tactics, resulting in adaptations that benefit males (in the short term) but not females (Le Galliard et al., 2005).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This hypothesis is supported by experimental studies, which indicate that male aggression toward females increases as a result of increased male–male competition in populations with male‐biased ASRs (Chapman, Arnqvist, Bangham, & Rowe, 2003; Le Galliard, Fitze, Ferrière, & Clobert, 2005), and this may be the main driver of female dispersal in some butterfly populations (Hovestadt & Nieminen, 2009). This process is hypothesized to be the evolutionary outcome of a sexual conflict over mating and reproduction tactics, resulting in adaptations that benefit males (in the short term) but not females (Le Galliard et al., 2005).…”
Section: Discussionmentioning
confidence: 84%
“…This hypothesis is supported by experimental studies, which indicate that male aggression toward females increases as a result of increased male–male competition in populations with male‐biased ASRs (Chapman, Arnqvist, Bangham, & Rowe, 2003; Le Galliard, Fitze, Ferrière, & Clobert, 2005), and this may be the main driver of female dispersal in some butterfly populations (Hovestadt & Nieminen, 2009). This process is hypothesized to be the evolutionary outcome of a sexual conflict over mating and reproduction tactics, resulting in adaptations that benefit males (in the short term) but not females (Le Galliard et al., 2005). Although sexual coercion is recognized as one of the key forces of sexual selection along with mate choice and mate competition and seems to be widespread in invertebrates, female harassment is known to exist in only a limited set of taxa in birds, for instance in waterbirds (Black, Choudhury, & Owen, 1996; McKinney, 1986) and passerines (Westcott, 1997).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, only two experimental studies, one with the lizard Lacerta vivipara (Le Galliard et al. 2005) and the other with the butterfly Pieris brassicae (Trochet et al. 2013), have focused on the effect of variation in sex ratio on adult movement.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies have assessed the movement of adults in response to manipulated sex ratio under seminatural conditions (Le Galliard et al. 2005; Trochet et al. 2013), and the authors of these studies concluded that the adult sex ratio is regulated by a balance between intra‐ and intersexual competition rather than by mate availability as suggested by theory (Perrin and Mazalov 2000).…”
Section: Introductionmentioning
confidence: 99%